2022
DOI: 10.1186/s12955-022-01994-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental and psychosocial health and health related quality of life before and after cardiac rehabilitation: a prospective cohort study with comparison to specific population norms

Abstract: Background Data on mental health improvement after cardiac rehabilitation (CR) are contradictory. The aim was to examine the mental and psycho-social health of patients admitted to our rehabilitation center following hospital treatment for acute coronary syndrome, before and after multidisciplinary CR. Methods Outcome was measured at admission and discharge by the 36-Item Short Form Survey (SF-36), the Symptom Checklist-90 Revised (SCL-90R), the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…They were referred by their family physician or a medical specialist to a specialized inpatient rehabilitation intervention tailored to their main medical diagnosis. The 6 cohorts comprised: ( i ) patients with whiplash-associated disorders (WAD) ( n = 71) who participated in the Zurzach Interdisciplinary Cervical Spine (Halswirbelsäule) concept (ZIHKo) ( 16 ); ( ii ) patients with low back pain ( n = 121) and ( iii ) those with fibromyalgia ( n = 84) who were treated in the Zurzach Interdisciplinary Pain (Schmerz) Program (ZISP) ( 17 ); ( iv ) patients with lower limb lipoedema ( n = 27) and ( v ) those with lymphoedema ( n = 78) of the lower extremity who took part in a complex physical decongestive therapy programme ( 18 ); and ( vi ) patients, who, after hospital treatment for acute coronary syndrome, participated in a multidisciplinary cardiac rehabilitation programme (post-acute coronary syndrome (post-ACS); n = 64) ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were referred by their family physician or a medical specialist to a specialized inpatient rehabilitation intervention tailored to their main medical diagnosis. The 6 cohorts comprised: ( i ) patients with whiplash-associated disorders (WAD) ( n = 71) who participated in the Zurzach Interdisciplinary Cervical Spine (Halswirbelsäule) concept (ZIHKo) ( 16 ); ( ii ) patients with low back pain ( n = 121) and ( iii ) those with fibromyalgia ( n = 84) who were treated in the Zurzach Interdisciplinary Pain (Schmerz) Program (ZISP) ( 17 ); ( iv ) patients with lower limb lipoedema ( n = 27) and ( v ) those with lymphoedema ( n = 78) of the lower extremity who took part in a complex physical decongestive therapy programme ( 18 ); and ( vi ) patients, who, after hospital treatment for acute coronary syndrome, participated in a multidisciplinary cardiac rehabilitation programme (post-acute coronary syndrome (post-ACS); n = 64) ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria for each programme together with the details of medical treatment can be found in the published reports on the individual cohorts (16)(17)(18)(19). Differences between the numbers of participants (n) included in the previous studies and in the current study are the result of the continuous recruitment of patients according to the inclusion criteria described in each publication.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression, anxiety, and fear of future cardiac events are common psychological challenges faced by heart patients [ 64 , 65 ]. A prospective cohort study demonstrated that engaging in CR led to noteworthy enhancements in mental and psychosocial health, along with improvements in health-related quality of life [ 66 ]. Similarly, another study highlighted the promising role of CR as a multidisciplinary approach in reducing depression and anxiety while enhancing overall quality of life [ 67 ].…”
Section: Reviewmentioning
confidence: 99%